Rethinking Common Versus Private Property. (March 2016) - Ellerman, David
Abstract: The Commons/Green Movement seems to have accepted that the current system is based on the principles of private property, and then has juxtaposed the notion of common property to private property. In fact, the current system is based on violations of the principle on which private ownership is supposed to rest, namely, the principle of people getting the fruits of their labor. The Commons Movement should critique the current system as an abuse of private property both in how it treats the products of labor as well as how it treats that which is not the fruits of anyone's labor (natural resources). When private property is refounded on its just foundation, then economic enterprises would be democratic firms such as worker cooperatives, and the ground would be cleared to apply special arrangements to natural resources, which are not the products of labor.